Gray's anatomy : the anatomical basis of medicine and surgery - Williams, Peter L; Bannister, Lawrence H; Berry, M; Collins, Patricia; Dyson, Mary; Dussek, Julian E; Ferguson, Mark W. J (Churchill Livingstone, 1995)
The publication focuses on human anatomy. Intended for professional public.
Keywords: anatomie; Anatomy